Sharia Business Development: Integrating Islamic Economic Principles with SDGs Goals - Erwan Iskandar; Eman Sulaiman (PT. Berkah Digital Teknologi, 2025)
Purpose of the Study – This study aims to analyze the relationship between Islamic economic principles and their role in supporting the achievement of Sustainable Development Goals (SDGs), particularly in sectors such as education, poverty alleviation, and renewable energy. The research also explores the effectiveness of innovative Sharia-compliant financial instruments, such as green sukuk and waqf-based funds, in addressing global sustainability challenges. Research Method – A mixed-method approach was employed, combining quantitative surveys with qualitative interviews. A sample of 205 respondents, including practitioners, policymakers, and stakeholders in Islamic finance, was analyzed using statistical techniques such as regression analysis, ANOVA, and path analysis to evaluate the relationships between variables and measure the effectiveness of Sharia-based instruments. Result – The findings indicate a significant positive relationship (β = 0.68, p < 0.01) between the application of Sharia principles and the achievement of SDGs, particularly in education and poverty alleviation. Moreover, 70% of respondents support the development of innovative financial instruments such as green sukuk, which was found to have a substantial impact (coefficient = 0.72) on financing renewable energy projects. However, challenges such as regulatory gaps and technical constraints were identified, highlighting the need for enhanced awareness and policy support. Conclusion – The study concludes that Islamic economic principles are highly relevant to achieving SDGs, particularly when integrated with innovative financial instruments. Practical implications include the need for regulatory frameworks to support Sharia-compliant financial products and increased collaboration among stakeholders to optimize their potential for sustainable development. Socially, the research underscores the importance of ethical finance in addressing global inequality and environmental challenges.